Caryolan-1-ol, an antifungal volatile produced by Streptomyces spp., inhibits the endomembrane system of fungi. Issue 7 (19th July 2017) - Cho, Gyeongjun; Kim, Junheon; Park, Chung Gyoo; Nislow, Corey; Weller, David M.; Kwak, Youn-Sig
Abstract : Abstract : Streptomyces spp. have the ability to produce a wide variety of secondary metabolites that interact with the environment. This study aimed to discover antifungal volatiles from the genus Streptomyces and to determine the mechanisms of inhibition. Volatiles identified from Streptomyces spp. included three major terpenes, geosmin, caryolan-1-ol and an unknown sesquiterpene. antiSMASH and KEGG predicted that the volatile terpene synthase gene clusters occur in the Streptomyces genome. Growth inhibition was observed when fungi were exposed to the volatiles. Biological activity of caryolan-1-ol has previously not been investigated. Fungal growth was inhibited in a dose-dependent manner by a mixture of the main volatiles, caryolan-1-ol and the unknown sesquiterpene, from Streptomyces sp. S4–7. Furthermore, synthesized caryolan-1-ol showed similar antifungal activity. Results of chemical-genomics profiling assays showed that caryolan-1-ol affected the endomembrane system by disrupting sphingolipid synthesis and normal vesicle trafficking in the fungi.